PELAKSANAAN PROGRAM KELUARGA HARAPAN DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA JELU AIR KECAMATAN JAWAI SELATAN - Antasalam, Arif; Syamsuri, Syamsuri; Purnama, Shilmy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research explains the implementation of the Family Hope Program in improving community welfare in Jelu Air Village, South Jawai District and explains the supporting and inhibiting factors for implementing the Family Hope Program in improving community welfare in Jelu Air Village, South Jawai District using a qualitative approach with descriptive methods. The results of the research are that the implementation of the Family Hope Program is going well with the stages of determining, receiving assistance, mentoring and updating data, but there are still obstacles faced, including problems with assistance and data updating. Apart from that, the Beneficiary Families of the Family Hope Program have carried out their obligations well as beneficiary participants even though some Beneficiary Families are still not aware of independent graduation. Then, the supporting factors for implementing the Family Hope Program are the socialization about the Family Hope Program which is carried out every year, the existence of activity plans which are always discussed with the participants of the Family Hope Program during each implementation, the support from the community and the skills carried out by the participants. The inhibiting factors are that there are no fixed indicators for revoking participation rights for those who are capable/independent, there is error data sent by the ministry that is not appropriate in the field.